Anatomical and Histological Study of Thyroid, Parathyroid and Ultimobranchial Glands in Iraqi Local Breed Turkey “Meleagris gallopavo”: r Mahmoud MirhishiShak and @m AliHanaa Karee - Ali, Hanaa Kareem (The Iraqi Journal of Veterinary Medicine, 2015)
The present study is designated to demonstrate the distinctive features, location, shape and boundaries, as well as the histological structures and the blood supply of the thyroid, parathyroid and ultimobranchial glands in the local breed turkey (Meleagris gallopavo). Twelve healthy birds from the local breed of Turkey were taken and divided into two equal groups: Six birds for anatomical study and six birds for histological study (three males and three females) for each study. Some anatomical parameters of the three glands which include: Length, width and volume, gross description, anatomical location and blood supply of the three glands were done. The anatomical results showed that the local breed Turkey has a pair of thyroid glands located in the thoracic inlet closely related to the common carotid artery and supplied with blood by three groups of arteries, the cranial thyroid, the middle thyroid and the caudal thyroid arteries. The mean length, width, weight and volume of the thyroid gland in turkey male were higher than in the female. Histologically thyroid gland enclosed by a thin collagenous capsule and consisted of spherical thyroid follicles lined by a single layer of epithelial cells enclosing a cavity filled with colloid and contain accessory parathyroid nodules between follicles. The Turkey bird also has asymmetrical pair of parathyroid glands, the right parathyroid gland located adjacent to the right thyroid gland while left one is being clearly separated from the left thyroid gland and located adjacent to or in contact with the left ultimobranchial gland medially to the common carotid artery, the gland in turkey is a single gland in all specimens. The mean length, width, weight and volume of the parathyroid gland in turkey female were more than in male. Histologically parathyroid gland is surrounded by collagenous capsule and composed of irregular anastomosing and branching cords of chief cells radiated about central sinusoids. The turkey bird also has a pair of ultimobranchial glands lying one on either side of the trachea, caudal to the parathyroid gland closely related to the bifurcation of the brachiocephalic artery. The mean length, width, weight and volume of ultimobranchial gland in turkey were of equal values between males and females. The gland composed histologically of different epithelial components including: C–cells or calcitonin–producing cells arranged as groups and loose cords, parathyroid nodules, vesicles or follicles of various shapes and sizes and cystic structure occupy most of the gland stroma. The mean length, width and volume of ultimobranchial founds in Turkey were similar in male and female.